Gaya Kepemimpinan untuk Account Representative pada Kantor Pelayanan Pajak di Wilayah DKI Jakarta - Maya Sari; Yanki Hartijasti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2018)
The purpose of this study is to investigate the current practices of leadership in Directorate General of Taxes, one of the public sectors in Indonesia. This study is also to determine the leadership style that is expected by employees. Respondents that were involved in this study were 550 Account Representatives and 68 Head of Supervision and Consultation Section from 17 Tax Offices (KPP) in the DKI Jakarta region. This study used a qualitative content analysis method. The results revealed that the current practices of leadership was the paternalistic leadership with the benevolent leadership dimension as the most widely displayed and considered as successful behavior. Meanwhile, leadership failure was due to lack of displayed the visible leadership dimensions and many displayed the authoritarian leadership dimension. The results also revealed a strong preference for paternalistic leadership with benevolent leadership dimension as the most expected behavior.